Preparação e investigação de eletrodos do tipo Ti/RuO2- SnO2-TiO2-Ta2O5 para eletroextração de zinco - Vasconcellos, Maria de Lourdes Soprani (2023)
Zinc is present in nature in the form of sulfide minerals, and its metallic form can be recovered through the electroextraction process with the aid of a lead anode. However, this material is polluting and requires high energy consumption from the system. To solve these problems, this study proposes replacing the lead anode with materials coated with titanium-based mixed oxide films, called dimensionally stable anodes (DSAs). The use of these anodes provides more sustainable and efficient alternatives during zinc electroextraction, thus contributing to reducing environmental impact and improving performance during industrial operation. Thus, the present work aimed to produce and investigate electrodes of ternary (Ti/RuO2-TiO2-SnO2, Ti/RuO2-SnO2- Ta2O5) and quaternary (Ti/RuO2-TiO2-SnO2-Ta2O5) compositions in different atomic proportions to study electroextraction of Zn2+ ions. The morphology of the films, examined by scanning electron microscopy, showed the formation of cracks on the surface of the metallic Ti substrate. During the accelerated life test (ALT), the Ti/RuO2- TiO2-SnO2 (45:50:4.7 atomic %) composition showed the longest operating time, equivalent to 4 hours. Electrochemical impedance spectroscopy (EIS) allowed the identification of the changes occurring on the surface of the DSA before and after ALT, taking into account the oxygen release region, at a potential of 1.4 V vs. RHE (reversible hydrogen electrode). The data obtained by EIS for the composition Ti/RuO2- TiO2-SnO2-Ta2O5 (42:32:4.8:17 atomic %) showed that this material supports extreme operating conditions (750 mA cm-2 , T = 25 °C), demonstrating that the combination of conducting oxide and semiconductor can modulate the stability of these electrodes. For the electroextraction of Zn2+, in H2SO4 0.5 mol L-1 and 2 mol L-1 media, all DSAs showed a lower cell potential variation than when using the Pb anode. The best results in terms of mass of electrodeposited Zn, reduction of Zn concentration in the initial solution and energy consumption were obtained for the following compositions studied Ti/RuO2-TiO2-SnO2 (45:50:4.7 atomic %); Ti/RuO2-SnO2-Ta2O5 (44:11:45 atomic %); Ti/RuO2-TiO2-SnO2-Ta2O5 (56:22:10:13 atomic %) and Ti/RuO2-TiO2-SnO2-Ta2O5 (40:32:06:21 atomic %). In 2 mol L-1 H2SO4 medium, the Pb electrode, Ti/RuO2-TiO2 (21:79 atomic %) and Ti/RuO2-TiO2-SnO2 (45:50:4.7 atomic %) showed agreement for the values of initial and final concentration of Zn as well as energy consumption. The DSAs Ti/RuO2-TiO2-SnO2-Ta2O5 (43:08:38:13 atomic %) and (40:32:06:21 atomic %) showed a correlation between the variation of the initial and final Zn2+ concentration, i.e. similar performance. The Ti/RuO2-SnO2-Ta2O5 (40:11:45 atomic %) composition was most influenced by the presence of Mn and Mg, which affected the electroextraction of Zn. The ADE Ti/RuO2-TiO2-SnO2-Ta2O5 (40:32:06:21 atomic %) showed 11% Zn2+ electroextraction with an energy consumption of 1.114 kWh/t, making it a viable material to replace the Pb anode in the industrial sector.